Synthetic Conditions and Color Characteristics of Tantalum Oxynitride Prepared via Liquid-NH3 Process - Yo Sasaki; Zentaro Tokuyasu; Yoichi Ono; Mitsunobu Iwasaki; Seishiro Ito (Advances in Materials Science and Engineering)
Tantalum oxynitrides, such as TaON, exhibit promising color properties and can be employed as nontoxic yellow pigments containing no heavy metals. We have developed a process for preparing nitrides or oxynitrides involving the vacuum-calcination of a precursor material obtained via reaction between a metal halide and liquid NH3. Herein, we describe the synthetic conditions of the liquid-NH3 process that affect the color, and thus the color characteristics, of the resulting pigments. Reaction and postreaction treatment conditions were adjusted to obtain the desired yellow color. The liquid-NH3 process was performed using 1.0 eq of H2O (relative to TaCl5) as the oxygen source and 30.0 eq of KCl (relative to TaCl5) as flux. Calcination of the precursor at 1073 K under vacuum was followed by recalcination from room temperature to 973 K at rate of 10 K min−1 under air. A powder with a color index of L∗=84.20, a∗=−2.71, and b∗=44.07 was obtained.